Global human mobility and knowledge transfer: Highly skilled return migrants as agents of transnational learning. (12th July 2022) - Lam, Alice; Rui, Huaichuan
Abstract: Global human mobility constitutes a key mechanism for knowledge transfer. This study examines the micro‐dynamics of knowledge transfer in the developed‐developing country migratory context. It highlights the agentic role of return migrants in transforming overseas learning into relevant knowledge in their home contexts. Drawing on situated and relational theories of knowledge and learning, the study views knowledge transfer as a relevance discovery process. It looks at a group of highly skilled migrants who had returned from developed countries to Ethiopia. Despite their high skill, the focus of knowledge transfer was mostly in non‐technical fields that include a broad range of organizational knowledge and work practices. These were made relevant to the local context through the returnees' 'work of reconciliation', involving 'engagement', 'alignment' and 'imagination'. The study challenges the standard assumption of a one‐way linear flow of knowledge from developed to developing countries. It sheds new light on the migration‐development link by highlighting the 'aspirational' aspect of migrant transnational learning.